Effects of quarantine on mental health of populations affected by Covid-19 - de Lima, Carlos Victor Chaves (J Affect Disord, 2020)
BACKGROUND: To prevent the spread of the The novel coronavirus (2019-nCOV), some classic public health measures are being taken, such as social distancing and quarantine METHOD: Studies were identified using large-circulation international journals found in two electronic databases: Scopus and Embase. RESULTS: The prolonged confinement is evidently related to psychological damage, considering that individuals would be subjected to stressors for a longer period of time . In some cases, these psychic losses lasted for many months after the end of this confinement CONCLUSIONS: It is necessary to develop and implement actions to minimize the population psychological distress in meeting the needs of the communities affected by COVID-19 Thus, as it occurred in China, it is necessary that the other affected nations promote the publication of regulations that guide the implementation of mental health services and the allocation of resources, in order to ensure that individuals are monitored by competent professionals, thus reducing the psychological damage that can be motivated by the social isolation period during the quarantine.